Step-by-step confinement diatomic catalyst, preparation method and application of step-by-step confinement diatomic catalyst in electro-catalytic synthesis of urea

By using a step-confined CuSn diatomic catalyst in the CO2 and NO3-co-reduction system, the problem of the catalyst being unable to simultaneously activate C and N substrates and inhibit competitive reactions was solved, and efficient urea synthesis was achieved with high yield and Faradaic efficiency.

CN119332295AActive Publication Date: 2025-01-21GUIZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411778632.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-21
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

In the urea system of CO2 and NO3-coreduction, it is difficult to achieve the ideal effect of urea yield and Faraday efficiency (FE), mainly because the catalyst cannot meet the co-activation and reduction of C and N substrates at the same time, and there are competitive reactions and Problems of complex product distribution.

Method used

Use CUSN dual -atomic catalysts with a level -oriented domain to form CEOX@SiO2 composite carrier by electrostatic adsorption of CEOX nano -glue on the gas phase SIO2 matrix, and then introduce CU and SN atoms on its surface to prepare CUSN/CEOX@SIO2 dual -atom catalyst catalyst Essence This catalyst has improved the efficiency of the C-N couplet reaction through high-active atoms separated and activated C and N species separated from the island.

Benefits of technology

The high urea yield range (24-56mmol H-1GCAT-1) and Faraday efficiency, and the catalyst still maintains stable activity after reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332295A_ABST
    Figure CN119332295A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of heterogeneous catalyst preparation and electro-catalytic synthesis of urea, in particular to a step-by-step confinement diatomic catalyst, a preparation method and application of the step-by-step confinement diatomic catalyst in electro-catalytic synthesis of urea. The preparation method comprises the following steps: dispersing gas-phase SiO2 in water, adding a Ce precursor, then adding an alkali solution for reaction, and calcining a precipitate obtained by the reaction to obtain CeOx-coated SiO2; the preparation method comprises the following steps: adding CeOx coated SiO2 into water, adding a Cu salt and a Sn salt, uniformly mixing, adding a Na2CO3 solution for deposition, and calcining and activating a solid obtained by deposition; according to the invention, gas-phase SiO2 is used as a matrix, and an ultra-small CeOx nano glue island is grafted on SiO2 through an electrostatic adsorption method. The uniformly dispersed CeOx is used as an atom carrier to limit Cu and Sn atoms on an island, so that the problems that an atomic-scale dispersed catalyst is easy to agglomerate at a high temperature, active sites are difficult to fully expose and the like are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of heterogeneous catalyst preparation and electrocatalytic synthesis of urea, and in particular to a step-by-step confined diatomic catalyst, a preparation method and application thereof in electrocatalytic synthesis of urea. Background Art

[0002] As human beings rely more and more on fossil energy, it has aroused widespread concern in energy security, environment and economy. Recent studies have found that greenhouse gases such as CO2 and NO3 - The electrocatalytic conversion technology using wastewater pollutants as raw materials can effectively synthesize urea, an important chemical nitrogen fertilizer. It is worth noting that urea, as a bulk industrial product, has adapted to the rapid growth of the world's population by contributing to the rapid development of agricultural production. However, traditional industry uses CO2 and NH3 to produce urea under harsh conditions of high temperature and high pressure. The acquisition of NH3 relies on the Haber-Bosch process, which will further cause environmental pollution and huge energy consumption. Based on the evaluation of the ease of obtaining raw materials and energy consumption, the development of NO 3- The application of electrocatalytic synthesis technology driven by renewable electricity to urea synthesis has great development significance for the reform of urea industry, while reducing water pollution and maximizing the utilization of waste resources.

[0003] Currently, CO2 and NO 3- In the co-reduction synthesis urea system, it is difficult to achieve the ideal urea yield and FE due to the formation of multiple carbon- and nitrogen-containing reduction products and the occurrence of competitive hydrogen evolution reaction (HER). Based on previous reports, in order to achieve both urea yield and FE, the following difficulties need to be overcome: 1) The catalyst needs to be able to simultaneously satisfy the co-activation and reduction of C and N substrates, 2) Optimize the adsorption energy of key C and N intermediates, 3) Inhibit the occurrence of competitive reactions that are not conducive to urea formation and avoid complex product distribution, 4) Construct highly selective multi-active sites to apply to the reduction of different substrates and form CN-coupled precursors, 5) The CN coupling process is feasible both thermodynamically and kinetically. Therefore, we actively develop catalysts with strong CO2 and NO 3- Electrocatalysts that have strong reducing ability and can selectively form intermediates that are beneficial to the synthesis of urea have become the top priority in overcoming many difficult problems.

[0004] Among many catalytic materials, atomically dispersed catalysts are an important development in the field of catalysis in recent years, especially in electrocatalytic reactions, showing significant potential and advantages. Traditional catalysts are often nanoparticles composed of multiple metal atoms, while atomically dispersed catalysts are single metal atoms highly dispersed on a carrier to form single atomic sites. This structure has unique catalytic performance and reaction selectivity. However, the current single-component atomically dispersed catalysts have the problems of a single active site, poor selectivity and low catalytic activity. Therefore, there is an urgent need to provide a diatomic catalyst with dual active sites to overcome the shortcomings of the existing technology. Summary of the invention

[0005] Based on the above content, the present invention provides a step-by-step confined diatomic catalyst, a preparation method and its application in electrocatalytic synthesis of urea. The step-by-step confined CuSn diatomic catalyst provided by the present invention overcomes the defects of the primary dispersed catalyst, such as poor dispersion effect, easy agglomeration and single active site.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] One of the technical solutions of the present invention is a method for preparing a step-by-step confined diatomic catalyst, comprising the following steps:

[0008] Step 1, dispersing gas phase SiO2 in water and adding Ce precursor to obtain a mixed solution;

[0009] Add an alkali solution to the mixed solution for reaction, and calcine the precipitate obtained by the reaction to obtain CeO x @SiO2;

[0010] Step 2: CeO x @SiO2 is added to water, and then Cu salt and Sn salt are added and mixed, and then Na2CO3 solution is added for deposition, and the deposited solid is calcined and activated to obtain the step-by-step confined diatomic catalyst (CuSn / CeO x @SiO2).

[0011] The second technical solution of the present invention is a step-by-step confined diatomic catalyst prepared according to the above-mentioned preparation method.

[0012] The third technical solution of the present invention is an electrode material, which is prepared by compounding the above-mentioned step-by-step confined diatomic catalyst with a matrix material.

[0013] The fourth technical solution of the present invention is that the above-mentioned step-by-step confined diatomic catalyst or the above-mentioned electrode material is used in the electrocatalytic reaction of CO2 and NO3 - Application in the synthesis of urea.

[0014] The fifth technical solution of the present invention is an electrocatalytic method for the reaction of CO2 and NO 3- The method for synthesizing urea is to place the above electrode material as a working electrode in a liquid containing NO3 - Urea is produced by CN coupling in a CO2-saturated electrolyte.

[0015] The present invention discloses the following technical effects:

[0016] 1. The present invention uses the abundant source and high specific surface area of ​​gas phase SiO2 as the matrix, and uses a simple electrostatic adsorption method to deposit ultra-small CeO x Nano-glue islands are grafted onto SiO2. Uniformly dispersed CeO x As an atomic carrier, Cu and Sn atoms are confined to the island, avoiding problems such as the agglomeration of atomically dispersed catalysts at high temperatures and the difficulty in fully exposing active sites.

[0017] 2. The CuSn diatomic catalyst prepared by the present invention is used to catalyze the urea synthesis reaction, with a yield of 24 to 56 mmol h -1 g cat -1 The higher urea yield range.

[0018] 3. The catalyst prepared by the present invention is of a heterogeneous type, which is easy to recover after the catalytic reaction is completed, and still maintains stable activity after being reused 9 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 These are X-ray diffraction spectra of the composite carriers and catalyst samples prepared in Examples 1-4 of the present invention; wherein a is the composite carrier prepared in Example 1, and b is the catalyst prepared in Examples 2-3.

[0021] Figure 2 Raman spectra of the composite carrier and catalyst samples prepared in Examples 1-4 of the present invention.

[0022] Figure 3 This is a high-angle annular dark-field scanning transmission electron microscopy image of the composite carrier prepared in Example 1 of the present invention.

[0023] Figure 4 Elemental mapping image of the catalyst prepared according to Example 4 of the present invention.

[0024] Figure 5 The extended X-ray absorption spectrum of the catalyst prepared in Example 4 of the present invention; wherein a is CuSn / CeO x @ Extended X-ray absorption fine structure spectrum of Cu K edge in SiO2, b is CuSn / CeO x @Extended X-ray absorption fine structure spectrum of Sn K-edge in SiO2.

[0025] Figure 6 The performance diagram of the composite carrier and catalyst samples prepared in Examples 1-4 of the present invention for catalyzing urea synthesis reaction under partial applied potentials; wherein a is CeO x @SiO2 Urea yield rate and urea Faraday efficiency (FE) corresponding to different applied potentials urea ), b is the distribution of Sn / CeO x @SiO2 corresponding to the urea yield and FEurea distribution at different applied potentials, c is Cu / CeO x @SiO2 corresponds to the urea yield and FEurea distribution at different applied potentials, d is CuSn / CeO x @SiO2 Urea yield and FEurea distribution corresponding to different applied potentials.

[0026] Figure 7 Performance diagram of the electrocatalytic urea synthesis stability test of the catalyst sample prepared in Example 4 of the present invention at -0.7V. DETAILED DESCRIPTION

[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0028] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0029] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0030] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0032] The diatomic catalyst of the present invention has two different metal atom active sites, one of which (Cu) can provide good catalytic activity, while the other (Sn) can adjust the structure and stability of the reaction intermediate, thereby improving the selectivity of the reaction. This synergistic effect enables the diatomic catalyst to significantly improve the reaction rate and product selectivity in the electrocatalytic reaction, and is particularly suitable for CN coupling reactions involving the reduction of two substrates.

[0033] The invention uses gas phase SiO2 with high specific surface area as the base material, and forms a precipitate with an electrostatic adsorption layer on the surface of SiO2 by using a Ce precursor (Ce(NO3)3·6H2O) under alkaline conditions; then forms a CeO2 with ultra-small size grafted on the SiO2 base under high temperature calcination. x Nano-gel island; CeO x The defects in the precipitate are used as anchoring points to support Cu and Sn atoms. CuSn / CeO is synthesized by calcining again. x @SiO2 diatomic catalyst.

[0034] The first aspect of the present invention provides a method for preparing a step-by-step confined diatomic catalyst, comprising the following steps:

[0035] Step 1, dispersing gas phase SiO2 in water and adding Ce precursor to obtain a mixed solution;

[0036] Add an alkali solution to the mixed solution for reaction, and calcine the precipitate obtained by the reaction to obtain CeO x @SiO2;

[0037] Step 2: CeO x @SiO2 is added to water, and then Cu salt and Sn salt are added and mixed, and then Na2CO3 solution is added for deposition, and the deposited solid is calcined and activated to obtain the step-by-step confined diatomic catalyst (CuSn / CeO x @SiO2).

[0038] In a preferred embodiment of the present invention, the molar ratio of the gas phase SiO2 to the Ce precursor is (6.0-15.0):(0.4-1.0). When the Ce precursor content is too high, the formed CeO x The nanoclusters are unevenly distributed or too large in size; when the Ce precursor content is too low, it will lead to CeO x It is not easy to form clusters or the cluster size is too small, which is not conducive to atomic loading; the Ce precursor is Ce(NO3)3·6H2O.

[0039] In a preferred embodiment of the present invention, the alkaline solution is aqueous ammonia; the amount of the alkaline solution added is such that the pH of the reaction system is 8-9.

[0040] In a preferred embodiment of the present invention, in step 1, the reaction time is 2-5 min; the calcination temperature is 450-550° C., and the calcination time is 10-24 h.

[0041] In step 1, after the reaction is completed, the method further comprises filtering out the precipitate and washing and drying the precipitate.

[0042] In a preferred embodiment of the present invention, the mass ratio of the CeOx@SiO2 to the Cu salt and the Sn salt is (0.1-0.2):(0.01-0.125):(0.005-0.1); the Cu salt is CuCl2; and the Sn salt is SnCl4.

[0043] In a preferred embodiment of the present invention, the Cu salt and Sn salt are added to the reaction system in the form of solutions. In some specific embodiments of the present invention, the concentration of the Cu salt solution is 50 mg mL -1 ; The concentration of the Sn salt solution is 50 mg mL -1 .

[0044] In a preferred embodiment of the present invention, in step 2, the mass ratio of Na2CO3 in the Na2CO3 solution to the Cu salt and the Sn salt is (0.65-2):(0.01-0.125):(0.005-0.1); the concentration of the Na2CO3 solution is 50 mg mL -1The deposition time is 4-6 hours; the calcination temperature is 550-650°C and the time is 12 hours; the activation temperature is 250-350°C and the time is 1 hour. In step 2, after the deposition is completed, the steps of filtering out the solid, washing and drying are also included.

[0045] The concentrations of the Cu salt solution, Sn salt solution and Na2CO3 solution in the present invention are only exemplary. The present invention does not impose any particular limitation on the concentrations of the Cu salt solution, Sn salt solution and Na2CO3 solution, and the mass ratio of Na2CO3 to Cu salt and Sn salt is (0.65-2):(0.01-0.125):(0.005-0.1).

[0046] In the present invention, Na2CO3 plays a role in precipitating Cu and Sn in the solution.

[0047] The second aspect of the present invention provides a step-by-step confined diatomic catalyst (CuSn / CeO x @SiO2).

[0048] CuSn / CeO prepared by the present invention x @The Cu and Sn atoms loaded on SiO2 are isolated from each other between islands. CuSn / CeO x @The contents of Cu and Sn atoms in SiO2 are 0.2-3.0wt% and 0.2-2.5wt%, respectively.

[0049] CeO x @The value range of x in SiO2 is 3-4.

[0050] The third aspect of the present invention provides an electrode material, which is prepared by compounding the above-mentioned stepwise confined diatomic catalyst with a matrix material.

[0051] The present invention does not specifically limit the type of base material, and any base material that can be used to prepare electrode materials known to those skilled in the art can be used. In some embodiments of the present invention, the base material is carbon paper.

[0052] The fourth aspect of the present invention provides a step-by-step confined diatomic catalyst or the electrode material for electrocatalytic conversion of CO2 and NO3 - Application in the synthesis of urea.

[0053] A fifth aspect of the present invention provides an electrocatalytic CO2 and NO 3- The method for synthesizing urea is to place the above electrode material as a working electrode in a liquid containing NO3 - Urea is produced by CN coupling in a CO2-saturated electrolyte.

[0054] In some embodiments of the present invention, the urea yield ranges from 24 to 56 mmol h -1 g cat -1 .

[0055] In some specific embodiments of the present invention, the CuSn / CeO x @SiO2 was prepared into electrode material by ultrasonically uniformly mixing with isopropanol, 5wt% naphthol (Nafion) solution and deionized water, and then reacted in KNO3 electrolyte solution saturated with CO2 to synthesize urea.

[0056] The electrode material is CuSn / CeO x @SiO2 loading is 0.1-0.2 mg cm -2 .

[0057] The urea synthesis reaction is carried out at room temperature, and the reaction time is 0.5 to 2 hours.

[0058] The reaction uses an H-type electrolytic cell as a reactor, AgCl / Ag as a reference electrode, Pt foil as a counter electrode, and the above electrode materials as working electrodes.

[0059] After the reaction is finished, the electrode loaded with the catalyst is directly taken out, and is repeatedly soaked and washed several times with deionized water, and can be used again for the electrocatalytic synthesis of urea after natural drying.

[0060] In the various solutions used in the specific embodiments of the present invention, unless otherwise specified, the solvent is water.

[0061] The method of the present invention firstly uses an electrostatic adsorption method to absorb CeO x Grafted on SiO2, CeO was obtained after high temperature calcination. x @SiO2 composite carrier. Then, Cu and Sn atoms are introduced on the carrier surface, and finally a CuSn diatomic catalyst is formed after high-temperature calcination. The highly active atoms separated by the islands efficiently capture and activate C and N species respectively, and use CO2-saturated KNO3 solution as electrolyte for electrocatalytic synthesis of urea at different application potentials, with good catalytic performance and Faraday efficiency.

[0062] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0063] The Nafion used in the embodiment of the present invention is a transparent liquid of DuPont brand model D520, with a volatile organic matter content of 50+3%, an exchange capacity of 1.03-1.12, and a resin solid content of 5%.

[0064] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0065] Example 1

[0066] 1. Composite carrier with step-by-step confinement effect (CeO x @SiO2, referred to as: composite carrier) preparation

[0067] (1) 0.72 g of fumed SiO2 was dispersed in 200 mL of deionized water and ultrasonicated for about 30 min. 0.8 mmol of Ce(NO3)3·6H2O was added under vigorous stirring.

[0068] (2) After the solid is completely dissolved, quickly add 1.6 mL of 2 mol L -1 NH3·H2O (the pH of the reaction system is 8.7 at this time), the precipitate is filtered out after reacting for 3 minutes, and washed with deionized water until neutral. The obtained colloidal solid is naturally dried at room temperature and calcined at 500℃ for 12h to obtain CeOx@SiO2.

[0069] 2. Catalytic activity test

[0070] 2mg CeO x @SiO2 was placed in 635μL isopropanol, 315μL deionized water and 50μL 5wt% naphthol solution and ultrasonically mixed for 40min to prepare catalyst ink. 50μL catalyst ink was drop-coated on 1×1cm carbon paper and used as working electrode after drying. Electrolysis was performed in CO2-saturated 0.1M KNO3 solution at room temperature using chronoamperometry (-0.5V to -1.0V) for 0.5h. The CO2 flow rate during the reaction was 30mL·min -1 .

[0071] The urea content was calculated using the urease decomposition method, and the urea generation rate was calculated to be 3.2 mmol h - 1 g cat -1 .

[0072] Example 2

[0073] 1. Step-by-step confinement of Sn single atom catalysts (Sn / CeO x @SiO2, referred to as catalyst) preparation

[0074] (1) 0.129 g of CeO prepared in Example 1 was added x @SiO2 and 10 mL of deionized water were ultrasonically mixed for 30 min, and 1 mL of 50 mg mL was added at 600 rpm. -1SnCl4 solution, stir well and add 13mL 50mg mL -1 The solid sample was filtered out and washed with deionized water and then dried naturally at room temperature.

[0075] (2) The solid sample was calcined at 600°C for 12 h and then activated at 300°C for 1 h in a hydrogen atmosphere to obtain a step-by-step confined Sn single atom catalyst.

[0076] 2. Catalytic activity test

[0077] The catalytic activity test is the same as in Example 1, except that CeO x @SiO2 replaced by Sn / CeO x @SiO2. The results showed that the urea generation rate was 11.81 mmol h -1 g cat -1 .

[0078] Example 3

[0079] 1. Cu single atom catalyst with gradual confinement (Cu / CeO x @SiO2, referred to as catalyst) preparation

[0080] (1) 0.129 g of CeO prepared in Example 1 was added x @SiO2 and 10 mL of deionized water were ultrasonically mixed for 30 min, and 2 mL of 50 mg mL was added at 600 rpm. -1 CuCl2 solution, stir well and add 13mL 50mg mL -1 The solid sample was filtered out and washed with deionized water and then dried naturally at room temperature.

[0081] (2) The solid sample was calcined at 600°C for 12 h, and then activated at 300°C for 1 h in a hydrogen atmosphere to obtain a step-by-step confined Cu single atom catalyst. (That is, the catalyst preparation conditions were exactly the same as those in Example 2, except that 1 mL 50 mg mL -1 SnCl4 solution was changed to 2mL 50mg mL -1 CuCl2 solution)

[0082] 2. Catalytic activity test

[0083] The catalytic activity test is the same as in Example 1, except that CeO x @SiO2 replaced by Cu / CeO x @SiO2. The results showed that the urea generation rate was 35.69 mmol h -1 gcat -1 .

[0084] Example 4

[0085] 1. Step-by-step confinement of CuSn diatomic catalysts (CuSn / CeO x @SiO2, referred to as catalyst) preparation

[0086] (1) 0.129 g of CeO prepared in Example 1 was added x @SiO2 and 10 mL of deionized water were ultrasonically mixed for 30 min, and 1 mL of 50 mg mL was added at 600 rpm. -1 SnCl4 solution and 2mL 50mg mL -1 CuCl2 solution, stir evenly and add 13mL 50mgmL -1 The Na2CO3 was deposited for 5 h. The solid sample was filtered out and washed with deionized water and then dried naturally at room temperature.

[0087] (2) The solid sample was calcined at 600°C for 12 h, and then activated at 300°C for 1 h in a hydrogen atmosphere to obtain a step-by-step confined Sn single atom catalyst. (That is, the catalyst preparation conditions were exactly the same as those in Example 2, except that 1 mL 50 mg mL -1 At the same time, 2 mL of 50 mg mL -1 CuCl2 solution)

[0088] 2. Catalytic activity test

[0089] The catalytic activity test is the same as in Example 1, except that CeO x @SiO2 replaced by CuSn / CeO x @SiO2 results showed that the urea generation rate was 55.81mmol h -1 g cat. -1 .

[0090] The composite carrier and catalyst samples obtained in Examples 1-4 were subjected to X-ray diffraction spectrum testing, and the results are as follows: Figure 1 As shown, the present invention successfully prepared CeO with step-by-step confinement effect. x @SiO2 composite support, the Sn, Cu single atoms and CuSn diatoms placed on the composite support did not agglomerate.

[0091] The composite carrier and catalyst samples obtained in Examples 1-4 were tested by Raman spectroscopy. Figure 2 As shown, the present invention converts CeO xAfter being compounded with SiO2, the catalyst underwent lattice distortion and abundant oxygen vacancy defects were generated.

[0092] Figure 3 This is a high-angle annular dark field scanning transmission electron microscope image of the composite carrier obtained in Example 1. Figure 3 It can be seen that the SiO2 surface is uniformly loaded with CeO x Nanogel islands.

[0093] Figure 4 This is the elemental mapping image of the step-by-step confined CuSn diatomic catalyst obtained in Example 4, demonstrating the uniform dispersion of Cu and Sn.

[0094] Figure 5 The X-ray absorption spectrum of the step-by-step confined CuSn diatomic catalyst prepared in Example 4 was expanded to study the local coordination environment of Cu and Sn atoms, proving that it has a diatomic structure.

[0095] Figure 6 The performance of the composite carrier and catalyst samples obtained in Examples 1-4 in electrocatalytic synthesis of urea proves that the CuSn diatomic catalyst has relatively ideal catalytic performance.

[0096] Figure 7 This is a stability test of the sample obtained in Example 4 in the urea synthesis reaction at an applied potential of -0.7 V, which proves that the CuSn diatomic catalyst has relatively good stability.

[0097] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a step-by-step confined diatomic catalyst, characterized in that: The following steps are involved: Step 1: Disperse gas-phase SiO2 in water and add a Ce precursor to obtain a mixed solution; add an alkali solution to the mixed solution for reaction, and calcine the precipitate obtained by the reaction to obtain CeO x @SiO2; Step 2: CeO x @SiO2 is added into water, and then Cu salt and Sn salt are added and mixed, and then Na2CO3 solution is added for deposition, and the deposited solid is calcined and activated to obtain the step-by-step confined diatomic catalyst.

2. The method for preparing a stepwise confined diatomic catalyst according to claim 1, characterized in that: The molar ratio of the gas phase SiO2 to the Ce precursor is (6.0-15.0):(0.4-1.0); the Ce precursor is Ce(NO3)3·6H2O.

3. The method for preparing a stepwise confined diatomic catalyst according to claim 1, characterized in that: The alkaline solution is aqueous ammonia; the amount of the alkaline solution added is such that the pH of the reaction system is 8-9.

4. The method for preparing a stepwise confined diatomic catalyst according to claim 1, characterized in that: In step 1, the reaction time is 2-5 minutes; the calcination temperature is 450-550° C., and the time is 10-24 hours.

5. The method for preparing a stepwise confined diatomic catalyst according to claim 1, characterized in that: The CeO x @The mass ratio of SiO2 to the Cu salt and Sn salt is (0.1-0.2):(0.01-0.125):(0.005-0.1); the Cu salt is CuCl2; the Sn salt is SnCl4.

6. The method for preparing a stepwise confined diatomic catalyst according to claim 1, characterized in that: In step 2, the mass ratio of Na2CO3 in the Na2CO3 solution to the Cu salt and the Sn salt is (0.65-2):(0.01-0.125):(0.005-0.1); the deposition time is 4-6h; the calcination temperature is 550-650°C, and the time is 12h; the activation temperature is 250-350°C, and the time is 1h.

7. A step-by-step confined diatomic catalyst prepared according to the preparation method according to any one of claims 1 to 6.

8. An electrode material, characterized in that: The catalyst is prepared by combining the step-by-step confined diatomic catalyst described in claim 7 with a bulk material.

9. The step-by-step confined diatomic catalyst according to claim 7 or the electrode material according to claim 8 in electrocatalysis of CO2 and NO3 - Application in the synthesis of urea.

10. An electrocatalytic CO2 and NO 3- A method for synthesizing urea, characterized in that The electrode material according to claim 8 is placed as a working electrode in a NO3 - Urea is produced by CN coupling in a CO2-saturated electrolyte.

Citation Information

Patent Citations

  • Preparation method of ruthenium-based ammonia synthesis catalyst with cerium oxide-silicon dioxide composite material as carrier

    CN110694623A

  • High-thermal-stability palladium monatomic catalyst as well as preparation method and application thereof

    CN117398999A

  • Method for synthesizing urea by electrocatalytic reduction of carbon dioxide and nitrate

    CN117431561A

  • Functional nanoscale metal oxides for stable metal single atom and cluster catalysts

    US20210016256A1